Relationship Between Knowledge and Attitudes Among Adolescent Toward Menarche of Psychological Response in The Junior High School, Siak - Rohmi Fadhli; Azmi Rofiani (Institute of Computer Science (IOCS), 2021)
Adolescence is an important time in a person’s development is marked by menarche in young women as well as changes both biologically and psychologically, causing psychological response to menarche is influenced by the knowledge and behavior of teenagers. The purpose of this study to determine the relationship of knowledge and attitudes of young women against psychological response at menarche in SMPN 5 Sungai Apit Kabupaten Siak. The design was analytic correlation with cross sectional approach. Analysis is univariate and bivariate analysis using purposive sampling counted 43 respondents. The result showed that there is a relationship between knowledge and attitudes of young women against psychological response at menarche in SMPN 5 Sungai Apit Kabupaten Siak with p value = 0,026 (p value< α=0,05), p value = 0,000 (p value< α=0,05). To the young or girls in SMPN 5 Sungai Apit Kabuaten Siak advised to seek information about the periods to get a good knowledge in order to get a positive attitude.